Unveiling the Eley–Rideal mechanism: H2 activation for nitrobenzene hydrogenation on nitrogen-doped carbon nanotubes - Hongquan Fu; Kuntao Huang; Jialong Zhang; Yonghai Cao; Hongjuan Wang; Hejun Gao; Yunwen Liao; Shuang Li; Hao Yu (Carbon Future)
Nitrogen-doped carbon nanotubes (NCNTs) emerge as an efficient metal-free catalyst for the hydrogenation of nitrobenzene to aniline, utilizing molecular hydrogen (H2) as the reducing agent. However, the mechanism of H2 activation on NCNTs is under debate so far. Here, we unveil the catalytic mechanism of NCNTs in this reaction through a comprehensive approach combining experimental and theoretical investigations. Our findings indicate that NCNTs are unable to directly dissociate H2 molecules, suggesting that the hydrogenation reaction does not proceed via the conventional Horiuti–Polanyi mechanism. Instead, we propose an Eley–Rideal mechanism, where H2 molecules are activated upon adsorption on the surface of NCNTs with adsorbed nitrobenzene molecules. Graphitic nitrogen (NG) and pyridine nitrogen (NP) are identified as the primary active sites. However, at higher nitrogen contents, the synergistic interaction between NP and NG is detrimental to catalytic activity, emphasizing that increased nitrogen content does not necessarily enhance performance. Further experiments demonstrate that, in addition to direct H2 activation, the transfer hydrogenation in protic solvents significantly boosts the overall reaction rate. Our work provides deep insights into the mechanism of H2 activation for the nitrobenzene hydrogenation catalyzed by NCNTs and offers theoretical guidance for the rational design of high-performance metal-free catalysts in catalytic hydrogenation reactions.